Investigating key elements of digital resilience among nursing undergraduates: a qualitative study - Li, Fanfan; Ma, Qiuping; Yang, Chunxiao; Zhong, Mingyang (Frontiers in Medicine, 2025)
Objective: To explore key elements of digital resilience in nursing undergraduates, providing a foundation for comprehensive assessment and training during medical colleges' digital transformation. 2 Methods: Conducted semi-structured interviews with 20 nursing undergraduates experienced in online learning or digital resource use from March-May 2024, utilizing descriptive qualitative research and directed content analysis. 3 Results: Identified five themes with nineteen sub-themes: understanding digital threats (information overload, decreased learning engagement, impaired social interaction, digital technology failures, digital security risks), knowing coping strategies (seeking teacher support, seeking peer support, seeking social support), learning knowledge and skills (nursing expertise, autonomous learning ability, digital technology application skills, digital learning skills, digital communication skills), overcoming digital threats stress (psychological resilience, continuous learning), and driving self-efficacy (self-regulation and motivational efficacy, online learning self-efficacy, digital skills self-efficacy, social interaction self-efficacy). 4 Conclusion: Nursing undergraduates' digital resilience is multifaceted. Medical colleges should strengthen these aspects to empower students to confidently navigate digital risks and adapt to educational and healthcare digital transformation.